Application of information technology for development of memory - Dopira, R.I.; Popova, N.V.; Polupan, K.L. (Publ.KarSU, 2017)
In the article processes occurring in memory are considered. The study of the laws of human memory, the mechanisms of its work is one of the central and most weighty chapters in psychology. Memory is special among other mental cognitive processes. The main processes are memorization, preservation, recognition and reproduction. The article describes the technologies that affect the expansion of memory boundaries. The authors describe the work of the Memory Tester application that is intended for the development of memory and imaginative thinking, increasing the volume and speed of memorizing and structuring information, expanding the field of view. The program implements memory development methods such as «Schulte's Table», «Highspeed memory», «Visual memory», «Mnemonic of words», «Mnemonic of numbers», «Pairs of words». The simulator contains a system of profiles, thanks to which several people can work on one computer. Each user of the program can choose one or another exercise program based on their memory features. The simulator will store the data of each user separately from each other. With this simulator, a person can find their weaknesses in memory and develop them or improve their strengths.
Жадыны дамытуға арналған ақпараттық технологияларды қолдану
Применение информационных технологий для развития памяти
Keywords: Memory; mental cognitive processes; expansion of memory boundaries; memory development methods; Memory Trainer; simulator; Schulte's table; high-speed memory; visual memory; mnemonic of words; mnemonic of numbers; pairs of words